581 Do job resources moderate the relationship between job demands and alcohol consumption or drug use?. (24th April 2018) - Van Rafelghem, E; Vander Elst, T; Delvaux, E; Van den Broeck, A; Baillien, E; Godderis, L
Abstract : Introduction: The Job Demands-Resources model predicts the direct and interaction effects of a wide range of job characteristics on employee well-being, but has hardly been used to predict work-related alcohol consumption and drug use. Based on this model, we expect that job demands increase the use of alcohol and drugs, whereas job resources are negatively related to the consumption. Furthermore, we hypothesise that job resources buffer the negative relationship between job demands and alcohol and drug use. Methods: Data were collected among employees in elementary and secondary schools in Belgium, using an online questionnaire (n=9, 790; response of 51.0%). Scientifically validated scales were used to measure qualitative job insecurity, work pressure, cognitive demands, social support, learning opportunities, task autonomy, alcohol consumption and drug use. The hypotheses were examined using hierarchical regression analysis in SPSS. Result: 92.5% of the participants were categorised as 'low risk' of problems related to alcohol consumption, 6.9% as 'medium risk' and 0.6% as 'high risk'. Furthermore, 93.3% were categorised as 'no problems' related to drug use, 6.1% as 'low level', 0.5% as 'moderate level', and 0.1% as 'substantial level'. Qualitative job insecurity was positively related to alcohol ( β =0.07; p<0.001) and drug abuse ( β =0.05; p < 0.01). Learning opportunities were negatively related to alcohol consumption ( β = -0.06; p < 0.01). Unexpectedly, task autonomy was positively related to alcohol consumption ( β = 0.04; p < 0.05). The other direct relationships as well as the interaction effects were not significant. Discussion: This study shows that qualitative job insecurity is an important determinant of employee alcohol and drug use. Furthermore, learning opportunities (negatively related) and task autonomy (positively related) may relate to alcohol consumption. Our findings will be discussed in light of their theoretical and practical contributions.